Is a Christian Transhumanism Possible? Theological Discernment, Conditions and Limits - González López, Jorge Ricardo (Razón y fe, 2026)
This article offers a typological synthesis of transhumanism—strong, moderate, and Christian—and demonstrates its usefulness for theological discernment. It identifies the movement’s religious and eschatological dimension—at times characterized as a “techno-gnostic religion”—and sets imago Dei and theosis as the norms of judgment. On this basis, morphological freedom is assessed according to three criteria: therapeutic purpose and proportionality; justice and non-discrimination; and eschatological coherence in the face of technosalvation. From this assessment a framework for a critical Christian transhumanism emerges, which is capable of admitting possibilities (restorative therapies, inclusive technologies) while delineating risks (materialist reductionism, objectification of the body, substitution of grace by technology). The novelty of the study lies in shifting the focus from merely descriptive typologies to a normative prudential judgment, articulated across dogmatic-fundamental, teleological-anthropological, and ethical-practical levels, thereby enabling the evaluation of concrete cases and, in turn, bringing into view the possibility of a Christian transhumanism.
Keywords: Christian transhumanism; strong transhumanism; weak transhumanism; morphological freedom; technognostic religion; imago Dei; theosis; eschatology